2019
DOI: 10.1364/ol.44.003992
|View full text |Cite
|
Sign up to set email alerts
|

Modal analysis for noise characterization and propagation in a femtosecond oscillator

Abstract: We study noise propagation dynamics in a femtosecond oscillator by injecting external noise on the pump intensity. We utilize a spectrally-resolved homodyne detection technique that enables simultaneous measurement of amplitude and phase quadrature noises of different spectral bands of the oscillator. To reveal the impact of added pump noise on the oscillator noise, we perform a modal analysis of the oscillator noise in which each mode corresponds to a particular temporal/spectral shape of the pulsed light. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the current experimental implementation is not yet a practical application to quantum secure communications, where the modes from the frequency comb need to be spatially separated and distributed to spatially distant parties, however, a standard technique in telecoms or spectroscopy can be used for separating frequency bins via dispersive optics. For instance, we adapted multimode homodyne detection, which has been performed in the spatial domain [49], to the frequency domain and used it to simultaneously measure the prepared modes within frequency pixels [50][51][52]. We have demonstrated that steering remains in that situation.…”
Section: Resolutionmentioning
confidence: 99%
“…Although the current experimental implementation is not yet a practical application to quantum secure communications, where the modes from the frequency comb need to be spatially separated and distributed to spatially distant parties, however, a standard technique in telecoms or spectroscopy can be used for separating frequency bins via dispersive optics. For instance, we adapted multimode homodyne detection, which has been performed in the spatial domain [49], to the frequency domain and used it to simultaneously measure the prepared modes within frequency pixels [50][51][52]. We have demonstrated that steering remains in that situation.…”
Section: Resolutionmentioning
confidence: 99%
“…Indeed, if a CF is represented by a 4D array, then coherent modes constitute 2D arrays and can be visualized in a 2D density plot. Second, the profiles of coherent modes and the distribution of their integral intensities give an additional insight into the light generation process [26,27]. Third, the propagation of a partially-coherent light beam can be viewed as an independent propagation of fully coherent modes.…”
Section: Coherent Modesmentioning
confidence: 99%